Are the official recommendations for amikacine serum levels suitable for older patients?. Issue 2 (12th March 2012) - Lajoinie, A.; Leroy, B.; Duquaire, M.; Gregoire, C.; Blot, A.; Maire, P.; Ducher, M.; Bourguignon, L.
Abstract : Background: The aminoglycosides represent the mainstay in the treatment of serious Gram-negative infections. Their use is difficult in older patients because of high potential toxicity and the large observed inter-individual variability. In recent years, higher peak serum concentrations have been suggested in official recommendations for amikacin treatment (peak level: 60 to 80 μg/ml, trough level: < 2.5 μg/ml). The applicability of these target concentrations is questionable in geriatric patients. Purpose: Our objective was to check the applicability of those target levels in older patients. Materials and methods: A retrospective study was undertaken with the medical files of all patients who were treated with amikacin during the last 3 years. Anthropometric data (age, weight, creatininemia) and history of amikacin administrations and serum levels were used to estimate individual pharmacokinetic parameters with a Bayesian software program (USC*Pack). The dosage regimen needed to reach a peak level of 60 µg/ml and a trough of 2.5 µg/ml was calculated. When a dose interval of more than 48 h was needed, a complementary calculation was done to estimate trough concentration after a week of treatment with infusions every two days. Results: Twenty-eight patients were considered, with a male/female ratio of 13/15, age 83±8 years, weight 64.2±3.7 kg and estimated creatinine clearance 55±21 ml/min. Mean estimated pharmacokinetic parameters were respectively: volume of distribution of 0.31±0.11 l/kg and amikacin clearance of 45.2±36.1 ml/min. Ideal dose interval was above 48 h for 12 patients (43%) with a mean dose interval of 62.5 h. For these patients, trough serum concentration level after a week of treatment, with infusions every two days, was 7.72±5.88 μg/ml. Conclusions: This study shows that for more than 40% of older patients, the target peak cannot be reached without potentially toxic trough levels even after 48 h, or without expanding the dose interval above. Such a wide dose interval can risk inefficacy for serious infections. For a large number of older patients, actual amikacin target serum concentrations should be used with caution to avoid potential toxicity.